Potential role of genipin in cancer therapy. (July 2018) - Shanmugam, Muthu K.; Shen, Hongyuan; Tang, Feng Ru; Arfuso, Frank; Rajesh, Mohanraj; Wang, Lingzhi; Kumar, Alan Prem; Bian, Jinsong; Goh, Boon Cher; Bishayee, Anupam; Sethi, Gautam
Graphical abstract: Abstract: Genipin, an aglycone derived from the iridoid glycoside, geniposide, is isolated and characterized from the extract of Gardenia jasminoides Ellis fruit (family Rubiaceae). It has long been used in traditional oriental medicine for the prevention and treatment of several inflammation driven diseases, including cancer. Genipin has been shown to have hepatoprotective activity acting as a potent antioxidant and inhibitor of mitochondrial uncoupling protein 2 (UCP2), and also reported to exert significant anticancer effects. It is an excellent crosslinking agent that helps to make novel sustained or delayed release nanoparticle formulations. In this review, we present the latest developments of genipin as an anticancer agent and briefly describe its diverse mechanism(s) of action. Several lines of evidence suggest that genipin is a potent inhibitor of UCP2, which functions as a tumor promoter in a variety of cancers, attenuates generation of reactive oxygen species and the expression of matrix metalloproteinase 2, as well as induces caspase-dependent apoptosis in vitro and in in vivo models. These finding suggests that genipin can serve as both a prominent anticancer agent as well as a potent crosslinking drug that may find useful application in several novel pharmaceutical formulations.